The Influence of Work-Life Balance on Employee Work Productivity with Work Creativity as a Mediating Variable (Study on Rattan Weaving MSMEs in Palangka Raya City) - Norliani; Roby Sambung; Vivy Kristinae; Indah Nur Oktavia (JURNAL ECONOMINA, 2026)
The purpose of this study is to examine how work-life balance influences employee productivity in micro, small, and medium enterprises (MSMEs) engaged in the rattan weaving industry in Palangka Raya City, with workplace creativity serving as a mediating variable. This research is motivated by the importance of work-life balance in supporting employee creativity and productivity within the creative MSME sector. Questionnaires were distributed to 39 respondents working in five MSMEs operating in the rattan weaving industry in Palangka Raya City to collect data using a quantitative research approach. With the assistance of SmartPLS software, the SEM-PLS method was employed to analyze the data. The findings indicate that work-life balance has a positive and significant effect on employee creativity and productivity. In addition, workplace creativity also has a positive and significant effect on work productivity. However, workplace creativity does not act as a mediating variable in the relationship between work-life balance and work productivity. These findings demonstrate that work-life balance plays a significant role in improving employee productivity in the rattan weaving craft industry in Palangka Raya City.